On Some Features of Osip Mandelstam’s Representation in the Memories by Anna Akhmatova - Galina Mikhailova (Literatūra (Vilnius), 2020)
The article presents some considerations on the motives for the creation and text strategies of Akhmatova’s memories of Mandelstam. The Pages from a Diary are viewed from two points of view: first, as a fragment of Akhmatova‘s memoir prose of a certain historical time, as an actualization of personal memory in order to correct collective cultural memory; secondly, as a supertext formed by numerous drafts, lists and variations. Within the framework of this genre, it is possible to single out a number of principles that Akhmatova is guided by when creating a memoir text: for example, a dialogical mode of a “conversation” with existing memories, documents, oral evidence; intention of myth-fighting, etc. A look at the Pages from a Diary as a work of narrative prose (based on Akhmatova’s definition of memories as a “short story”), called “The Death’s Way,” allows us to add the hero of her memoir to a number of “damned poets” that are not alien to Mandelstam.